Enfoque del cuidado humanizado de enfermería durante el trabajo de parto. - Calvopiña Riera, Katherine Mishell (2022)
Humanization in labor care is considered in recent years as a health care strategy, given the obstetric violence that has existed for many years in health facilities worldwide. Currently, humanized childbirth is characterized by respect for its normal physiological process, in order to reduce the use of medications and unnecessary invasive procedures in women giving birth; the humanization of childbirth focuses on the rights, values, beliefs, customs, and feelings of pregnant women, taking into account their physical and emotional needs that the nursing staff must satisfy to create a positive childbirth experience. The general objective is to determine the approach to humanized nursing care through Jean Watson's theory during labor. 105 bibliographic sources from different databases were reviewed and after applying inclusion and exclusion criteria, a sample of 74 bibliographic sources was obtained, 37 of them were used for the triangulation process. Based on the results, qualities of humanized care were determined, such as: individualized care, facilitating family and staff support, reducing pain through non-pharmacological techniques, advising on free position childbirth, management of childbirth with intercultural belonging, and promoting its mammalization.